Investigating the biosynthesis and roles of the auxin phenylacetic acid during Pseudomonas syringae-Arabidopsis thaliana pathogenesis - Lee, Chia-Yun; Harper, Christopher P.; Lee, Soon Goo; Qi, Yunci; Clay, Taylor; Aoi, Yuki; Jez, Joseph M.; Kasahara, Hiroyuki; Blodgett, Joshua A. V.; Kunkel, Barbara N. (Frontiers in Plant Science, 2024)
Several plant-associated microbes synthesize the auxinic plant growth regulator phenylacetic acid (PAA) in culture; however, the role of PAA in plant-pathogen interactions is not well understood. In this study, we investigated the role of PAA during interactions between the phytopathogenic bacterium Pseudomonas syringae strain PtoDC3000 (PtoDC3000) and the model plant host, Arabidopsis thaliana. Previous work demonstrated that indole-3-acetaldehyde dehydrogenase A (AldA) of PtoDC3000 converts indole-3-acetaldehyde (IAAld) to the auxin indole-3-acetic acid (IAA). Here, we further demonstrated the biochemical versatility of AldA by conducting substrate screening and steadystate kinetic analyses, and showed that AldA can use both IAAld and phenylacetaldehyde as substrates to produce IAA and PAA, respectively. Quantification of auxin in infected plant tissue showed that AldA-dependent synthesis of either IAA or PAA by PtoDC3000 does not contribute significantly to the increase in auxin levels in infected A. thaliana leaves. Using available arogenate dehydratase (adt) mutant lines of A. thaliana compromised for PAA synthesis, we observed that a reduction in PAA-Asp and PAA-Glu is correlated with elevated levels of IAA and increased susceptibility. These results provide evidence that PAA/IAA homeostasis in A. thaliana influences the outcome of plant-microbial interactions.